Killer systems in Saccharomyces cerevisiae: three distinct modes of exclusion of M2 double-stranded RNA by three species of double-stranded RNA, M1, L-A-E, and L-A-HN. - Wickner, R B (1983)
M1 and M2 double-stranded RNAs (dsRNAs) code for the K1R1 and K2R2 killer toxin and resistance functions, respectively. Natural variants of a larger dsRNA (L-A) carry various combinations of the [EXL], [HOK], and [NEX] genes, which affect the K1 and K2 killer systems. Other dsRNAs, the same size as L-A, called L-B and L-C, are often present with L-A. We show that K1 killer strains have [HOK] and [NEX] but not [EXL] on their L-A (in disagreement with Field et al., Cell 31:193-200, 1982). These strains also carry other L-size molecules detectable after heat-curing has eliminated L-A. The exclusion of M2 dsRNA observed on mating K2 strains with K1 strains is due to the M1 dsRNA (not the L-A dsRNA as claimed by Field et al.) in the K1 strains. Four independent mutants of a [KIL-k2] [NEX-o] [HOK-o] strain were selected for resistance to [EXL] exclusion of M2 ([EXLR] phenotype). The [EXLR] phenotype showed non-Mendelian inheritance in each case, and these mutants had simultaneously each acquired [HOK]. The mutations were located on L-A and not on M2, and did not confer resistance to M1 exclusion of M2.